Hand Cut Sentence for Corruptors (Thematic Study of Tafsir Ahkam Surah Al-Maidah Verse 38) - Firqah Annajiyah Mansyurah (Syariah: Jurnal Hukum dan Pemikiran, 2019)
Abstract: Corruption is one of the most hated and combated criminal acts, because corruptors are grasped as taking away people’s welfare. At present, the penalties for corruptors are considered too light, so that many people think corruptors had better punished by cutting their hands. The call to enforce the law of cutting hands on perpetrators of corruption gets an idea from the law for thieves as stated in the Alquran surah Al-Maidah verse 38. But the big question is whether corruptors can be associated to the terms of the thief so that they can be punished by hand. Therefore the author feels the need for a thematic study of the interpretation of the Alquran surah Al-Maidah verse 38 in order to answer this question, in order to get clarity whether the meaning of theft can be equated with acts of corruption. The method that author use in this paper is a qualitative descriptive study with the main references to book of interpretations, hadis books and fiqh books relating to the law of cutting hands. The results of the study that author get, it turns out Al-Maidah verse 38 cannot be applied to criminal acts of corruption because the term thief in the verse is not the same as the corruptor. Keywords: sharia law, corruptors, cutting hands, tafsir ahkam Abstrak: Korupsi adalah salah satu tindakan pidana yang paling dibenci dan diperangi, karena koruptor dianggap merenggut kesejahteraan rakyat banyak. Saat ini, hukuman untuk koruptor dianggap terlalu ringan sehingga banyak orang berpendapat agar koruptor dihukumi dengan hukuman potong tangan. Seruan untuk memberlakukan hukum potong tangan pada pelaku korupsi mendapat gagasan dari hukum bagi pencuri seperti yang telah tertuang pada Alquran surah Al-Maidah ayat 38. Namun yang menjadi pertanyaan besar adalah apakah koruptor bisa disamakan seperti term pencuri pada ayat tersebut sehingga bisa diberikan hukuman potong tangan. Oleh karena itu penulis merasa perlunya kajian tematik tafsir Alquran surah Al-Maidah ayat 38 guna menjawab pertanyaan tersebut, agar mendapatkan kejelasan apakah makna pencurian bisa disejajarkan dengan perbuatan korupsi. Metode yang penulis gunakan dalam tulisan ini adalah penelitian deskriptif kualitatif dengan rujukan utama kitab-kitab tafsir, kitab-kitab hadis dan kitab fikih yang berkaitan dengan hukum potong tangan. Hasil kajian yang penulis dapatkan, ternyata Al-Maidah ayat 38 tidak bisa diterapkan pada tindak pidana korupsi karena term pencuri pada ayat tersebut tidaksama dengan koruptor.